High performance Athletes dual career support opportunities in the context of the European Union - Ābeļkalns, Ilvis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article aims to provide an overview of high performance athletes - students dual-career support opportunities in the European Union, in order to create dual career support system in Latvia. The paper provides an explanation of terms, and analyzes the UK, Ireland, Germany, Belgium and other countries' experience in the dual career. In the process is created a comparative overview of the possibilities for support in several European countries. High-performance athletes main types of support are flexible exam schedule, individual study plan, consultations with lecturers, distance learning studies (e-learning), the mentor's advice, and reduced requirements for entrance exams. In Latvia there is not created united support system, each university tries to find support for their athletes at their own discretion.